2017
DOI: 10.1016/j.envint.2017.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Serum polychlorinated biphenyls and leukocyte telomere length in a highly-exposed population: The Anniston Community Health Survey

Abstract: Background Serum polychlorinated biphenyls (PCBs) have previously been associated with longer leukocyte telomere length (LTL) in most, but not all, of the few previous studies. PCBs were produced in Anniston, Alabama from 1929–1971 and participants of the Anniston Community Health Survey (ACHS) were highly exposed. Objectives We evaluated serum levels of 35 PCBs and relative telomere length in 559 ACHS participants. Methods Relative LTL was measured in DNA extracted from blood clots. We assessed PCBs indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 64 publications
0
14
1
Order By: Relevance
“…2016)], persistent organic pollutants (POPs) (Mitro et al. 2016), polychlorinated biphenyls (PCBs) (Callahan et al. 2017), and benzene (Bassig et al.…”
Section: Discussionmentioning
confidence: 99%
“…2016)], persistent organic pollutants (POPs) (Mitro et al. 2016), polychlorinated biphenyls (PCBs) (Callahan et al. 2017), and benzene (Bassig et al.…”
Section: Discussionmentioning
confidence: 99%
“…The residents were interviewed and had blood samples taken for serum level measurement of 35 PCB congeners, serum lipids, and DNA isolation. We measured DNA methylation in a subset (n = 518) of the ACHS-I cohort members using DNA from stored frozen blood clot samples [5].…”
Section: Study Populationmentioning
confidence: 99%
“…In 2005, the Anniston Community Health Survey was established to assess the health effects of general population PCB exposure (ACHS-I) with a follow-up study conducted in 2014 (ACHS-II) [1,2]. Previous ACHS-I studies reported associations between PCB exposure and race [1], hypertension [3], blood pressure [4], leukocyte telomere length [5], liver disease [6], metabolic syndrome [7], serum lipid levels [8], and diabetes [9]. Several previous population studies have found associations between PCB or dioxin exposures and altered blood DNA methylation levels in Dutch men [10], Greenlandic Inuits [11], Koreans [12], Faroe Islanders [13] and Japanese [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to studying cancer, researchers have begun to examine associations between exposures to environmental chemicals and biomarkers of effect with potential relevance for cancer, including telomere length (TL) (15)(16)(17)(18)(19). Telomeres are complexes of repetitive DNA sequences and proteins that cap the ends of chromosomes to protect against degradation and fusion during cell division (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…While the literature on the PFAS and TL relationship seems equivocal, such studies may not be comparable due to underlying differences in study populations, methodological approaches, and other confounding and modifying factors.Our results show that PFAS exposure is associated with telomere lengthening. Previous work has shown that exposure to environmental chemicals is associated with longer TL(16,19,99,100) Mitro et al, 2016. proposed that certain POPs, particularly polychlorinated…”
mentioning
confidence: 99%